Axial force at the blade - Kleshnev, V. (BioRow, 2021)
The finer points of oar mechanics were previously analysed in RBN 2020/12: discrepancies between propulsive forces derived at the blade and rower-boat system were found, and a hypothesis was raised about the possible contribution of the blade axial force. Since then, we have tried different ways of measuring the blade axial force directly with a sensor built in the shaft close to the blade. However, attempts were unsatisfactory because of high crosstalk from a large torque created by normal blade force. So, it was decided that axial blade force Fba would be determined indirectly, as a difference between the handle Fha and gate Fga axial forces. Concluding, the axial blade force was found to be quite significant: it can create up to a 70N braking force with two blades at oar angles 55deg, which is similar to the drag at the boat hull. Therefore, blade resistance at its axial movement through the water should be minimised.